Loss of privacy in electronic payment systems - Aleksandra Pešterac; Nenad Tomić (Anali Ekonomskog fakulteta u Subotici, 2020)
The emergence of new information technologies such as the Internet of Things, the fifth generation of mobile Internet, artificial intelligence, Big Data, machine learning and blockchain, has led to significant changes in the social and business environment. The potential for exponential growth in such conditions is also recognized in the field of electronic payment systems. The development of the Internet of Things, as a global technical infrastructure that connects objects by adding microprocessors and communications software to them, has become an important basis for the further progress of electronic payment systems. In the process of further improvements, the system faces the great challenge of protection against the unauthorized use, modification or destruction of data. An even greater challenge is the potential abuse of users' personal data by business entities or government agencies. The paper focuses on the challenges of protecting the privacy of users of electronic payment systems in a smart environment.